Comparison of risk profile in pre-menopausal and post-menopausal women with acute coronary syndrome - Chhabra, Sandeep; Dhooria, Harmeet Pal S.; Garg, Avantika; Dhooria, Gurdeep S. (International Journal of Research in Medical Sciences, 2020)
Background: The physiological changes associated with menopause are responsible for increase in cardiovascular disease after menopause. BMI, physical inactivity, metabolic syndrome, hypertension and diabetes mellitus increase in post-menopausal women which are all powerful predictors of cardiovascular events. The risk factor profile between pre-menopausal and post-menopausal women presenting with acute coronary syndrome was thus studied. Methods: This study was a prospective cross-sectional hospital based study and was conducted in the Department of Medicine and Department of Cardiology, Dayanand Medical College and Hospital, Ludhiana wherein 50 pre-menopausal women and 50 post- menopausal women who presented with acute coronary syndrome were enrolled. The risk factor profile and angiography findings amongst the 2 groups were compared. Results: There was no difference in the incidence of Diabetes Mellitus and Hypertension among the pre & post-menopausal groups. The prevalence of family history of cardiovascular disease was higher in the pre-menopausal group. The post-menopausal women showed a significant decrease in physical activity due to sedentary lifestyle. Both the groups had high BMI and increased waist circumference. Lipid parameters did not show any significant difference between the two groups. However, pre-menopausal women had higher LDL-C and triglyceride levels and lower HDL-C levels. On analysis of the angiographic findings in diabetics and non-diabetics, of both the groups diabetes mellitus was much higher in subjects presenting with triple vessel disease suggesting extensive atherosclerosis. Conclusions: study showed physical inactivity as an important cardiovascular risk factor in post-menopausal women. Obesity is an important risk factor for coronary artery disease in both pre- and post-menopausal women.